2023
DOI: 10.1002/adfm.202300860
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Dimensional 2‐thiopheneethylammonium Lead Halide Capping Layer Enables Efficient Single‐Junction Methylamine‐Free Wide‐Bandgap and Tandem Perovskite Solar Cells

Abstract: Wide‐bandgap (WBG) perovskite solar cells (PSCs) have garnered significant attention for their potential applications in tandem solar cells. However, their large open‐circuit voltage (VOC) deficit and serious photo‐induced halide segregation remain the main challenges that impede their applications. Herein, a post‐treatment strategy without thermal annealing is presented to form a 2D top layer of 2‐thiopheneethylammonium lead halide (n = 1) on WBG perovskites. This thermal annealing‐free post‐treatment method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Compared to the P0 absorber, which does not include Pb(SCN) 2 additive, all absorbers including 2 mol % Pb(SCN) 2 exhibit reduced FWHM, indicating an improved grain morphology. Additionally, a peak near ∼5.5°was observed in the lower-angle XRD, originating from the main (002) diffraction peak of the 2D TEA 2 PbX 4 RP phase 16,38 as shown in Figure S2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to the P0 absorber, which does not include Pb(SCN) 2 additive, all absorbers including 2 mol % Pb(SCN) 2 exhibit reduced FWHM, indicating an improved grain morphology. Additionally, a peak near ∼5.5°was observed in the lower-angle XRD, originating from the main (002) diffraction peak of the 2D TEA 2 PbX 4 RP phase 16,38 as shown in Figure S2.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the charge distribution is substantially reduced from ∼9.49 × 10 17 cm –3 (P2) to ∼2.71 × 10 17 cm –3 (P2T1) at the edge of the carrier profile ( N CV IF ). The formation of 2D perovskite (TEA 2 PbX 4 ) is reported to shift the Fermi energy level and valence band maximum to downward, thereby creating a hole barrier at the interface (C 60 /2D/3D perovskite). This barrier at the interface effectively inhibits undesired recombination at the C 60 /perovskite interface, ,, and this reduction in recombination is also supported by the 3.5-fold decrease in defects density at the interface ( N CV IF ) of TEACl-treated P2T1 device.…”
Section: Resultsmentioning
confidence: 99%
“…[29] In a separate study, Zhu et al employed an in situ protonation process by adding polyethylenimine family into Cs 0.25 (MA 0.01 FA 0.99 ) 0.75 Pb(I 0.85 Br 0.15 ) 3 perovskite precursors, effectively reducing deep-level traps and enabling 1.65 eV bandgap PSCs with a PCE of 22.33% and a V OC deficit of 0.45 V. [31] In addition to additives, post-treatment strategies have been widely adopted to reduce interface defects and align energy levels between perovskites and charge transport layers. [32][33][34][35][36] For instance, Liu et al reported a grain regrowth and bifacial passivation tactic to minimize nonradiative recombination losses in FA 0.8 Cs 0.15 MA 0.05 Pb(I 0.82 Br 0.18 ) 3 perovskites, yielding a high PCE of 21.90% with a small V OC deficit of 0.43 V. [34] However, it is important to note that most highly efficient WBG PSCs have thus far necessitated the incorporation of volatile methylamine (MA) cation into perovskite films, [30,31,34] which has proven particularly detrimental to the long-term stability of the devices. [32] In addition, significant V OC losses persist, particularly in mixed iodide/bromide systems (E g > 1.63 eV), posing challenges in achieving a V OC deficit lower than 0.40 V compared to their normal-bandgap (1.55 eV) counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35][36] For instance, Liu et al reported a grain regrowth and bifacial passivation tactic to minimize nonradiative recombination losses in FA 0.8 Cs 0.15 MA 0.05 Pb(I 0.82 Br 0.18 ) 3 perovskites, yielding a high PCE of 21.90% with a small V OC deficit of 0.43 V. [34] However, it is important to note that most highly efficient WBG PSCs have thus far necessitated the incorporation of volatile methylamine (MA) cation into perovskite films, [30,31,34] which has proven particularly detrimental to the long-term stability of the devices. [32] In addition, significant V OC losses persist, particularly in mixed iodide/bromide systems (E g > 1.63 eV), posing challenges in achieving a V OC deficit lower than 0.40 V compared to their normal-bandgap (1.55 eV) counterparts. [37] Therefore, it is imperative to explore approaches that further reduce the V OC deficit and mitigate photo-induced halide segregation in MA-free WBG PSCs to bolster device performance and stability.…”
Section: Introductionmentioning
confidence: 99%